Fetal cerebellum growth curve by ultrasound in twin pregnancies and in pregnancies with fetal growth alterations. Preliminary report - Pacheco Romero, José (2015)
OBJETIVE: To determine the growth curve of the fetal cerebellum in twin or impaired fetal development pregnancy. DESIGN: Prospective, cross Preliminary study. MATERIALS AND METHODS: the transverse cerebellar diameter was determined in 73 pairs of twin fetuses, 13 fetuses with IUGR and 12 large for gestational age fetuses. The study was conducted at the Department of Obstetrics ultrasound Edgardo Rebagliati Martins National Hospital, EsSalud, Lima, Peru. For statistical analysis, the Epi-Info version 6.0 software was used. RESULTS: The growth curve of cerebellar diameter (DC) found in fetal twins seemed somewhat higher than in singleton pregnancy until week 30, after growing at a similar rate of singleton pregnancy; the correlation coefficient was r = 0.89 and confidence limits 95%, 0.83 <r <0.93. In the growth curve in the DC term fetuses with IUGR (preeclamptic mothers), no difference was observed between measurements 50 percentile in IUGR fetuses compared with normal singleton fetuses, except slightly smaller diameter at 38 and 39 weeks. In large fetuses for gestational age (LGA) of non-diabetic mothers, DC seemed somewhat higher in fetuses GEG weeks 38 and 40. CONCLUSIONS: The DC can determine fetal growth in multi-fetal pregnancy, is diagnostic clinician growth restriction and does not seem to overestimate, gestational age of the fetus GEG. Larger studies on the growth of fetal cerebellar diameter in complicated pregnancies, in order to corroborate these findings is required.